Visualisasi Iklan Televisi dan Ekspresi Seni pada Anak Penderita Autis - Anne Nurfarina (ITB Journal Publisher, LPPM ITB, 2009)
Autism Spectrum Disorder (ASD) is a complex neurobehavioral disorder characterized by impairment in reciprocal social interaction, impairment in communication, and the presence of repetitive and stereotypic patterns of behaviors, interest, and activities. Autism Spectrum Disorder has grown to epidemic proportions, once to be very rare that ASD are estimated to occur in as many as 1:160 (one in every 160 people). Although autism is characterized by deficits in socialization, communication and imagination; they still have. This paper will focus on perceptual creativity processing. As Kientz & Dunn,1977 said that Children with autism show sensitivities to visual and other stimuli in everyday life For example; parents have reported that their autistic children show interested to look at the TV commercial, which is the audio and visual from the program influences her/his mood to stimulating creative activities such as painting. Television, from children's programs through commercial television, has probably influence to people life styles. Such ways of interesting of autistic children to this program have real implication how the subject stimulated for anyone. Some works of art by the autistics shown connection between the audio visual media and ideas of creative activities. It is now possible, using television commercial methods to make a child with autism rise their abilities. By using the purposive sampling methods, the research focused some Aan's (15 years old) works.